THE HEALTH EDUCATION AND ITS APPLICATIONS IN HEALTH SURVEILLANCE - Pereira Soares da Silva Portácio, Sylas Rhuan; Araújo Fraga, Antônio Carlos (Cadernos ESP, 2023)
To describe the main health education practices and their possibilities for health surveillance. This work is structured based on an integrative literature review, focusing on articles published in the last 10 years. 184 articles were retrieved, which 110 were published in the last 10 years in full text. 98 articles were excluded by the exclusion criteria, totaling 12 articles included in this study. The publications brought light to a series of actions and themes in health education that are connected and can be extrapolated to the field of health surveillance. This work recognizes health education as an important ally of VISA professionals, and its importance for the safety and quality of life of the population, goods and services. Finally, it emphasizes the need and encourages new studies aimed at proving the effectiveness of the actions proposed here in the field of VISA.